Determination of Consumptive Behavior in Economic Education Students of Semarang State University with Lifestyle Variables as Mediation - Wijayanto, Wikan Nur; Oktarina, Nina; Rusdarti (Universitas Negeri Semarang, 2025)
Consumptive behavior refers to the tendency of individuals or groups to purchase goods and services excessively for purposes beyond basic needs, often to express identity or achieve personal satisfaction. This study aims to analyze the influence of peers, social media, self-control, and financial literacy on the consumptive behavior of Economic Education students at Universitas Negeri Semarang with lifestyle as a mediating variable. Using a quantitative approach, the research involved 195 students selected from a population of 381. Data were collected through a validated and reliable questionnaire and analyzed using descriptive statistics, classical assumption tests, path analysis, and the Sobel test. The findings show that lifestyle significantly mediates the effects of peers, social media, self-control, and financial literacy on consumptive behavior. The results imply that students should be more selective in responding to peer influence, social media exposure, and advertising stimuli, while also developing stronger self-control and financial literacy through workshops, seminars, or training programs. Strengthening these aspects can help students make more rational financial decisions and reduce tendencies toward consumptive behavior.